2006
DOI: 10.1007/bf02936533
|View full text |Cite
|
Sign up to set email alerts
|

The management of patients who require temporary reversal of vitamin K antagonists for surgery: a practical guide for clinicians

Abstract: The management of patients who require temporary interruption of vitamin K antagonists is a common clinical problem, affecting an estimated 400 000 patients per year in Europe and North America. Managing such patients is challenging because of the lack of randomized trials assessing different perioperative anticoagulation management strategies and inconsistent recommendations from consensus groups. Recent non-randomized trials have helped to estimate the risks for arterial thromboembolism and bleeding with bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Several studies have been concerned with heparin-bridging therapy before invasive procedures or surgery, and bridging therapy is generally recommended in AF patients with a high TE risk [8,[16][17][18][19][20][21][22]. Because two large randomized trials are currently under way, it is important to determine whether bridging therapy before invasive procedures or surgery is also needed in patients with low to moderate TE risk [39,40].…”
Section: Heparin-bridging Therapy At Oac Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been concerned with heparin-bridging therapy before invasive procedures or surgery, and bridging therapy is generally recommended in AF patients with a high TE risk [8,[16][17][18][19][20][21][22]. Because two large randomized trials are currently under way, it is important to determine whether bridging therapy before invasive procedures or surgery is also needed in patients with low to moderate TE risk [39,40].…”
Section: Heparin-bridging Therapy At Oac Initiationmentioning
confidence: 99%
“…The frequency of heparin bridging in OAC initiation is variously reported to range from 5% to 64% in several retrospective studies [12][13][14][15]. Because 25-50% of patients with AF are asked to interrupt OAC before an invasive procedure or surgery every year, many studies have been published concerning the risk and benefit of bridging anticoagulation, and current international guidelines recommend the use of bridging therapy in AF patients undergoing interruptions of warfarin who are considered to be at high thromboembolic (TE) risk, such as patients with prosthetic heart valves, venous thromboembolism, valvular AF, or AF with higher CHADS 2 scores (estimates risk based on the presence of congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, and prior stroke or transient ischemic attack) [8,[16][17][18][19][20][21][22]. Several studies have demonstrated the reduction of hospital stay [12] and risk of VTE and death [13] in patients who received bridging therapy with heparin.…”
Section: Introductionmentioning
confidence: 99%
“…19) Intravenous administration of vitamin K has a slight risk of severe anaphylactoid reaction and should only be given by slow intravenous infusion (over 20-30 minutes) and more rapid reversal is achieved. 20) This mode of vitamin K administration in case of emergency is widely adopted throughout the world, including at our center. In the present study, the majority of episodes of CT could be managed successfully by immediate drainage and reversal of anticoagulation with protamine sulfate (11 patients) and vitamin K1 intravenously (3 patients) simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ÔbridgingÕ therapy with unfractionated heparin (UFH) or low-molecular-weight heparin (LMWH) is usually implemented in patients considered to be at intermediate-tohigh risk of TE, such as those with prosthetic heart valves or atrial fibrillation [3][4][5][6][7][8]. Intravenous heparin is attractive as bridging therapy because of its rapid onset of action and short half-life, thus minimizing the exposure time to low anticoagulation [9]; however, such an approach is not easily practicable.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous heparin is attractive as bridging therapy because of its rapid onset of action and short half-life, thus minimizing the exposure time to low anticoagulation [9]; however, such an approach is not easily practicable. The use of LMWH is feasible but its optimal management in this setting is uncertain [3][4][5][6][7][8][9][10]. Another potential strategy is to continue oral anticoagulation therapy with a temporary adjustment of warfarin intensity to a preoperative international normalized ratio (INR) of 1.5-2.0, but such an approach has shown a high rate of bleeding [11].…”
Section: Introductionmentioning
confidence: 99%